Alkaline Earth–Olefin Complexes with Secondary Interactions. Issue 19 (31st March 2016) - Roşca, Sorin‐Claudiu; Dinoi, Chiara; Caytan, Elsa; Dorcet, Vincent; Etienne, Michel; Carpentier, Jean‐François; Sarazin, Yann
Abstract: Strontium and calcium (alkaline earth: Ae) olefin complexes stabilised by secondary Ae⋅⋅⋅F−C and β‐agostic Ae⋅⋅⋅H−Si interactions are presented. Olefin coordination onto the alkaline earths is plain in the solid state, and it is thermodynamically favoured over the coordination of THF. The existence of the Ae⋅⋅⋅olefin interactions is corroborated by solution NMR data and DFT computations. The coordination mode of the olefin varies with steric effects and, if enforced, olefin dissociation can be compensated by the other non‐covalent interactions, as supported by DFT computations. Abstract : Several heteroleptic strontium and calcium (Ae) olefin complexes stabilised by a pattern of secondary Ae⋅⋅⋅F−C and β‐agostic Ae⋅⋅⋅H−Si interactions have been structurally authenticated. The nature of the non‐covalent interaction between olefin and metal is discussed.